Evaluation of Toxicity of some Novel Molecules of Insecticides against Spodoptera litura (FAB.) - Bhatnagar, Shiwani; Kumar, Arvind; Karnatak, A. K.; Kumar, Yogesh (Indian Forester, 2013)
An attempt was made to assess the toxicity of some novel molecules of insecticides against Spodoptera litura (Fab.). The dose mortality response to the 7 d old larvae of S. litura indicated that spinosad at 24 h was 4.773 times more toxic than cartap hydrochloride at LC50 value. By the lapse of time this ratio further increases to 82.5 at 48 h and 71 times at 72h. The relative toxicity ratio (RTR) of novel molecules at LC50 value in comparison to cartap hydrochloride at 24h and 48h were: spinosad (4.77, 9.9)> fipronil (1.59, 3) and at 72h the values were spinosad (10.14) and fipronil (2.54). LC50 values of cartap hydrochloride, fipronil, spinosad, as 0.44% and 0.126%; 0.0418% and 0.079%; 0.004% and 0.0264% respectively at 24 h.